2014
DOI: 10.1002/etc.2771
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a water quality guideline for aluminium in marine waters

Abstract: Metal risk assessment of industrialized harbors and coastal marine waters requires the application of robust water quality guidelines to determine the likelihood of biological impacts. Currently there is no such guideline available for aluminium in marine waters. A water quality guideline of 24 µg total Al/L has been developed for aluminium in marine waters based on chronic 10% inhibition or effect concentrations (IC10 or EC10) and no-observed-effect concentrations (NOECs) from 11 species (2 literature values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 28 publications
5
51
1
2
Order By: Relevance
“…This is consistent with known mechanisms of toxicity from precipitated forms of Al in fish that are related to smothering of gill surfaces and increased mucus production at the gills, thereby limiting respiratory gas exchange [29][30][31][32]. Similar mechanisms are likely responsible for toxicity from exposure to precipitated forms of Al in invertebrates [5], and both precipitated and dissolved forms of Al have been shown to contribute to algae toxicity [5,33]. Therefore, Al toxicity under circumneutral conditions should best be expressed and modeled on the basis of both dissolved and precipitated Al, rather than dissolved or monomeric Al, as would be preferred at more acidic pH [16].…”
Section: Discussionsupporting
confidence: 83%
“…This is consistent with known mechanisms of toxicity from precipitated forms of Al in fish that are related to smothering of gill surfaces and increased mucus production at the gills, thereby limiting respiratory gas exchange [29][30][31][32]. Similar mechanisms are likely responsible for toxicity from exposure to precipitated forms of Al in invertebrates [5], and both precipitated and dissolved forms of Al have been shown to contribute to algae toxicity [5,33]. Therefore, Al toxicity under circumneutral conditions should best be expressed and modeled on the basis of both dissolved and precipitated Al, rather than dissolved or monomeric Al, as would be preferred at more acidic pH [16].…”
Section: Discussionsupporting
confidence: 83%
“…Vrieling et al (1999) found that the increased Al positively affected the growth and final cell density of pennate Navicula salinarum, but not of centric species Thalassiosira weissflogii; while Saçan (2007) found that Al negatively affected the growth of diatom Minutocellus polymorphus and green alga Dunaliella tertiolecta. However, a limited Al effect was observed for the growth of diatom Skeletonema costatum (Stoffyn 1979); and no significant effects were detected on the brown macroalga Hormosira banksii, sea urchin embryo Heliocidaris tuberculata and 2 juvenile fish species of Lates calcarifer and Acanthochromis polyacanthus, even at an extremely high Al level (37 μmol l -1 ) (Golding 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Aluminium (Al), gallium (Ga), and molybdenum (Mo) are 3 metals for which there is little chronic toxicity information available for marine species and which are of relevance to tropical marine waters. A recent study has derived a high-reliability guideline value of 24 mg/L Al for marine waters [5]. However, in some regions, including tropical northern Australia, dissolved Al in coastal seawater can range from 10 mg/L to 16 mg/L in the dry season to 20 mg/L to 29 mg/L in the wet season depending on the vicinity to freshwater inputs [4].…”
Section: Introductionmentioning
confidence: 99%